Effect of blade rotation in the water - Kleshnev, V. (BioRow, 2021)
Previously, in RBN 2021/10, it was hypothesised that the rotation of the blade in the water during the drive may consume energy and reduce the propulsive force and power within the rower-boat system, and here we provide further analysis of this effect.